TOUCH AND FEEL Tails - Sajnani, Surya (London, United Kingdom : Happy Yak, 2022)
Meet seven cute animals with terrific tales, from a swirling seahorse to a busy beaver.
Keywords: Senses and sensation -- Juvenile literature; Ear -- Juvenile literature; Animals -- Juvenile literature; Textured books; Board books